2002
DOI: 10.1364/ao.41.002947
|View full text |Cite
|
Sign up to set email alerts
|

Compensation of birefringence in active elements with a novel Faraday mirror operating at high average power

Abstract: A decrease in the depolarization ratio by more than one order of magnitude by use of a recently proposed Faraday mirror (FM) in comparison with the traditional FM has been demonstrated experimentally. At a high average laser power, the possibility of an increase in the accuracy of compensation of depolarization in the active element by means of a lambda/4 plate with both the traditional and the novel FM is shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…These devices are among those in which thermal self-action of laser radiation is most pronounced due to relatively high absorption (∼10 −3 1/cm) in magneto-optical elements (MOEs) and the need to use relatively long MOEs (∼1-2 cm). Thermally induced birefringence arising in magneto-optical elements fully determines the efficiency of the devices at high average power of transmitted radiation [5], [6]. Thus, search for methods to reduce and compensate thermal effects in Faraday devices [7], as well as search and study of the properties of new magneto-active materials with better mechanical and thermo-optical properties are of current importance.…”
mentioning
confidence: 99%
“…These devices are among those in which thermal self-action of laser radiation is most pronounced due to relatively high absorption (∼10 −3 1/cm) in magneto-optical elements (MOEs) and the need to use relatively long MOEs (∼1-2 cm). Thermally induced birefringence arising in magneto-optical elements fully determines the efficiency of the devices at high average power of transmitted radiation [5], [6]. Thus, search for methods to reduce and compensate thermal effects in Faraday devices [7], as well as search and study of the properties of new magneto-active materials with better mechanical and thermo-optical properties are of current importance.…”
mentioning
confidence: 99%
“…Since a laser beam induces (being a heat source) and simultaneously reads distortions, the value of self-action may depend significantly on the transverse distribution of the intensity. The results obtained can be generalized for an arbitrary axially symmetric beam (Khazanov et al, 2002b), including a super-Gaussian beam with power P 0 and intensity…”
Section: The Influence Of Beam Shapementioning
confidence: 94%
“…In (Khazanov et al, 2002b) it was shown that [001] is the best orientation. The absorption coefficient α 0 at 1064nm wavelength in TGG can vary by several times from sample to sample, see Table 1, where values of V and κ are also included.…”
Section: Selection Of Magneto-optical Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…These Faraday rotators can also compensate the thermally induced birefringence in the amplifiers. 25,26 The SBS-PCM used in this experiment is composed of a SBS cell and a concave mirror as depicted in Fig. 2.…”
mentioning
confidence: 99%